Improving English Vocabulary for Young Learners Through Memrise Application - Pardamean, Pardamean; Santoso, Didik (EXCELLENCE: Journal of English and English Education, 2025)
This study investigates whether the memrise application can improve English vocabulary skills among young learners. Recognizing the important role of vocabulary in language acquisition. The study used an action research with a sample of 30 primary school students, utilizing quantitative data and qualitative data to evaluate how the memrise application can improve English vocabulary skills. The results revealed a significant improvement in vocabulary skills, with students’ mean scores increasing from 45.1 to 83.4 after implementing the application. Memrise’s key features, like gamification, spaced repetition, and multimedia resources, contributed to increased engagement and effective learning. Qualitative feedback indicated that students found the learning process enjoyable and motivating, creating a sense of competition among students and increasing their willingness to participate in the learning process. This study suggests that the memrise application can improve English vocabulary skills among young learners. The findings advocate the integration of innovative apps into the language learning process to drive better educational outcomes.